Uniqueness results for Zakharov-Kuznetsov equation. Issue 6 (3rd June 2019) - Cossetti, Lucrezia; Fanelli, Luca; Linares, Felipe
Abstract: In this paper we study uniqueness properties of solutions to the Zakharov-Kuznetsov equation of plasma physic. Given two sufficiently regular solutions u 1, u 2, we prove that, if u 1 − u 2 decays fast enough at two distinct times, then u 1 ≡ u 2 .